THE NON-NATIVE TEACHER: INTERVIEW WITH PROF. PEÌTER MEDGYES - Floris, Flora Debora (TEFLIN Journal, 2018)
PeÌter Medgyes, CBE, is Professor Emeritus of Applied Linguistics and Language Pedagogy. During his career he was a schoolteacher, teacher trainer, vice rector, vice president of IATEFL, deputy state secretary and ambassador of Hungary. He was a plenary speaker in over fifty countries and author of numerous books and papers published both in his home country and abroad. His most recent book is the third edition of The Non-native Teacher (Swan Communication, 2017). His main professional interests lie in teacher education, language policy and humour research.